2019
DOI: 10.1016/j.humpath.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the IDO1/TDO2-AhR pathway in tumor cells or the tumor microenvironment is associated with Merkel cell polyomavirus status and prognosis in Merkel cell carcinoma

Abstract: Merkel cell carcinoma (MCC) is a rare, aggressive neuroendocrine skin cancer, with approximately 80% of cases related to Merkel cell polyomavirus (MCPyV). Indoleamine 2,3-dioxygenase 1 (IDO1) and tryptophan 2,3-dioxygenase 2 (TDO2) are the key rate-limiting enzymes of the tryptophan to kynurenine (KYN) metabolic pathway. With aryl hydrocarbon receptor (AhR), an intracellular transcription factor, they play a role in escaping the immunosurveillance process in several cancers. IDO1/TDO2/AhR expression associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
2
18
1
Order By: Relevance
“…29 Similarly, glioma cells with high TDO expression grew faster and had a higher proliferation index than TDO-deficient control tumours in vivo. 12,[33][34][35] Using the P815 mouse tumour model, Pilotte found that compared to control tumours, TDO-expressing tumours grew faster and more potently inhibited local T lymphocyte proliferation. 12 In conclusion, our data show that overexpression of TDO promotes the proliferation and invasion of HCC cells in vitro and in vivo and indicate that TDO might serve as an effective biomarker for diagnosis and prognosis and a promising target for therapy in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…29 Similarly, glioma cells with high TDO expression grew faster and had a higher proliferation index than TDO-deficient control tumours in vivo. 12,[33][34][35] Using the P815 mouse tumour model, Pilotte found that compared to control tumours, TDO-expressing tumours grew faster and more potently inhibited local T lymphocyte proliferation. 12 In conclusion, our data show that overexpression of TDO promotes the proliferation and invasion of HCC cells in vitro and in vivo and indicate that TDO might serve as an effective biomarker for diagnosis and prognosis and a promising target for therapy in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, MCC carcinogenesis is associated with the oncogenic Merkel cell polyomavirus (MCPyV), while in the other cases, it is UV-driven [1]. MCCs are heterogeneous tumors that are often infiltrated by various immune and stromal cells [2]. While the role of tumorinfiltrating lymphocytes has been studied in detail [3][4][5], the characteristics of tumor-associated fibroblasts in the MCC microenvironment are largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…MCC is a rare and aggressive neuroendocrine skin cancer, and ~80% of patients are infected with merkel cell polyomavirus. Univariate analysis of clinical specimens revealed that a longer overall survival is achieved in the group with lower expression of tryptophan 2,3-dioxygenase 2 (TDO2) and AHR in cells surrounding the tumor (70). As TDO2 is an enzyme in the tryptophan-kynurenine metabolic pathway, the TDO2-AHR axis may play a significant role in the pathophysiology of MCC.…”
Section: Maintenance Of Skin Cancer Via Ahr Activationmentioning
confidence: 99%